1989
DOI: 10.3109/00016488909127519
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Immunotherapy for Head and Neck Cancer with Killer Cells Induced by Stimulation with Autologous or Allogeneic Tumour Cells and Recombinant Interleukin-2

Abstract: Peripheral blood lymphocytes drawn by leukapheresis using Haemonetics V50 were mixed and cultured with autologous or allogeneic tumour cell line to activate killer cells by tumour antigenic stimulation, and further with recombinant interleukin-2 (rIL-2). Killer cells were intra-arterially infused, as a primary therapy, in 5 patients with maxillary and one with lingual cancer (squamous cell carcinoma). Effects on reduction of primary tumour size were significantly high without any severe side effects. The effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Other tumors such as melanoma and renal cell carcinoma have been studied in greater depth and have shown some clinical response to immunotherapeutic treatments. Previous immunotherapeutic trials in HNSCC patients have studied the toxicity and efficacy of interleukin (ID‐2 infused intravenously or injected into the peritumoral or perilymphatic region of cancer patients 1–21 . Findings from these trials have revealed that between 0% and 65% of patients have shown a clinical response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Other tumors such as melanoma and renal cell carcinoma have been studied in greater depth and have shown some clinical response to immunotherapeutic treatments. Previous immunotherapeutic trials in HNSCC patients have studied the toxicity and efficacy of interleukin (ID‐2 infused intravenously or injected into the peritumoral or perilymphatic region of cancer patients 1–21 . Findings from these trials have revealed that between 0% and 65% of patients have shown a clinical response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…28) In fact, Vα14 NKT cells infected with the retrovirus-mediated IL-2 gene survive significantly longer in vitro than Vα14 NKT cells infected with control retrovirus (unpublished observation). Patients undergoing LAK therapy sometimes receive IL-2, [29][30][31][32] but administration of IL-2 to cancer patients can produce serious side effects including febricula, pleural effusion, gastrointestinal perforation, insanity, etc. ; therefore, the clinical usage of cultured Vα14 NKT cells with IL-2 might be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In head and neck cancer regional low-dose IL-2 treat ment alone [13][14][15] or in combination with LAK cells [ 17,18] has been investigated. Despite some encouraging ini tial results the therapeutic value of this approach has not been established, and several host-and treatment-related parameters which may be associated with successful im munotherapy have to be determined.…”
Section: Discussionmentioning
confidence: 99%